Single Parent Parenting in Early Childhood Social and Emotional Development. - Azkia Fajri Al-Aisyi; Aan Listiana (Exploration in Early Childhood Research, 2024)
This research aims to analyze single parent parenting on the social and emotional development of early childhood through a systematic literature review method. Children need a process to develop, every child's development requires support from the environment around them. The first environment that influences children is the family. Parents play a role in the growth and development of their children. Parents are the first people to provide care and education to children. If parents divorce, it will affect their social and emotional development. The systematic literature review method was used to collect and analyze findings from previous research relevant to this topic. This research will provide an overview of single parent parenting on the social and emotional development of early childhood. The results of this research show that parenting carried out by single parents by inviting children to discuss, tell each other stories and express their opinions is a way for parents, both mothers and fathers, to continue to provide care, provide love and time for children amidst the limited presence of complete parents and there is good communication between father and mother and children so that children do not feel abandoned due to divorce.